Low Level of Serum Immunoglobulin G Is Beneficial to Clinical Cure Obtained With Pegylated Interferon Therapy in Inactive Surface Antigen Carriers - Li, Hong; Lin, Xiao; Liu, Lili; Qin, Ling; Zheng, Yanhong; Liu, Xiaohui; Wei, Xinhuan; Liang, Shan; Liu, Yali; Zhang, Jing; Chen, Xinyue; Cao, Zhenhuan (Frontiers in Immunology, 2022)
Purpose Our recent study showed a high rate of HBsAg clearance in inactive HBsAg carriers (IHCs) treated with pegylated IFN (PEG-IFN). To better understand the immune-mediated component of HBsAg clearance, this study investigated the role of serum immunoglobulin G (IgG) and its subclasses in predicting HBsAg clearance in IHCs with PEG-IFN therapy. Methods In this study, IHCs received PEG-IFN for 96 weeks. Subjects who achieved clearance of HBsAg were considered responders (R group), and those in whom HBsAg was not cleared were considered non-responders (NR group). The HBsAg, ALT, and serum lgG subtypes (lgG1, IgG2, IgG3, lgG4) were tested at baseline, and at 12 and 24 weeks of treatment. To evaluate the factors in predicting HBsAg clearance, univariate and multivariate logistic regression analyses were performed. The receiver operator characteristic curves and the area under the receiver operator characteristic curve (AUROC) were used to evaluate prognostic values. Results Our results showed that 39 cases obtained HBsAg clearance (group R), while 21 cases did not (group NR). There was no significant difference in age, ALT, and AST levels between the two groups. The serum levels of IgG1, lgG2, lgG3 and lgG4 at baseline, and at 12 and 24 weeks were significantly lower in IHC with HBsAg clearance than in the NR group. Univariate logistic regression analysis showed that serum IgG1, IgG2, IgG3, and IgG4 levels at baseline, and at 12, and 24 weeks were all strong predictors of HBsAg clearance. In all indicators, lgG2 had the highest AUROC at baseline and lgG3 the highest AUROC at week 12. A multifactor logistic analysis was performed with y=33.933-0.001*BaselinelgG1-0.002*BaselinelgG2. The area under the curve was 0.941 with 100% sensitivity and 76.19% specificity. Conclusion Together, our findings suggest that serum IgG has a higher predictive value compared to the convention predictors of HBsAg and ALT for HBsAg clearance and thus may be a better clinical predictor of HBsAg clearance in IHCs.